A SYSTEMATIC APPROACH TO TEACHING MORPHEMİC TO PUPILS OF THE UZBEK SCHOOL - Makhmudova D.S. (American Journals Publishing, 2023)
This article discusses the difference in morphemic and word-formation of languages. Knowledge of the laws of word formation of the Russian language, the ability to determine the meaning of word-formation morphemes contribute to the expansion of the child's vocabulary, the enrichment of the grammatical structure of his speech, and his understanding of the grammatical system of the Russian language as a whole.
Keywords: morphemes, modeling, prefix, affix, prefixes, point of view.